(untitled) (Perner’s Contacts, 2011)
The article deals with methods multi-criteria decision can be applied for evaluation the quality of public transport. The article is an analysis of methods of determining weights of criteria, methods of multi-criteria decision and their evaluation in terms of their use for evaluation the quality of public transport.